Kinematic differences according to the types of front leg roundhouse kicks in taekwondo - Ryu, S.; Park, S.-K.; Park, J.-M.; Oh, H.-R.; Jung, K.-C. (Korean Journal of Sport Biomechanics, 2024)
Objective: This study aims to examine the kinematic differences between the types of front leg roundhouse kicks in Taekwondo. Method: The participants were 9 male Taekwondo athletes (Age: 20.6 ± 1.3 years, Height: 185.7 ± 7.6 cm, Body Weight: 69.7 ± 13.8 kg, Career: 10.6 ± 2.7 years). Each participant performed six trials of Apbal-Dollyeochagi (front leg roundhouse kick [AD]) and Balbutyeo-Dollyeochagi (foot to foot roundhouse kick [BD]). The three most successful scoring attempts for each type were analyzed. The analysis phases were divided into reaction phase (P1), preparation phase (P2), and kicking phase (P3). Kinematic parameters such as the anterior-posterior (A/P) movement of the center of mass (COM), lower limb segment velocity, joint angles, and angular velocities were calculated to compare the two techniques. Results: In the P1, the AD exhibited a shorter execution time than the BD (p<.05). During the P1 and P2, the A/P displacement of the COM was smaller in the AD compared to the BD, while the displacement was larger during the P3 (p<.05). Additionally, joint angle differences were observed between the two techniques across all phases (p<.05). Conclusion: These findings suggest that the AD can be effectively utilized for its quick reaction time and suitability for short distances. On the other hand, the BD can be advantageous for managing distances through A/P movement adjustments.